Mathematical Model to Determine the Relationship Between Road Traffic Flow, Vehicle Speed and Road Traffic Gridlock in a Road Link - Igbinosun, L.I.; Omosigho, S.E. (Agriculture and Natural Resources, 2015)
The effects of the frequency and the speed of vehicles on road traffic gridlock were examined. Steady state queueing models were used to develop a mathematical relationship between the road traffic frequency of vehicles, the speed of vehicles and road traffic congestion. The model was applied to both a single lane and a double lane road. The results showed a substantial rise in the number of vehicles in the queue for a very low speed beyond some value(s) called the critical value(s) of speed. The work explains why there is road traffic congestion on some roads without seeing the actual cause. It also provides a clue to the theoretical approach to the management of road traffic congestion and underscores the need to engage in serious scientific study of congestion on roads as opposed to the ad hoc strategies currently employed in Nigeria to address road traffic congestion.